Pragmatic Acts in Selected Culture-Based Plays of Ahmed Yerima (2014)
Culture is central to Ahmed Yerima‟s dramaturgy, and his culture-based dramatic texts largely project the cultural values of the three major ethnic groups in Nigeria, namely, Yoruba, Hausa and Igbo. Existing linguistic studies on Yerima‟s plays have concentrated on the use of proverbs and politeness features, ignoring an in- depth pragmatic study of their cultural contexts. This study, therefore, undertakes an investigation of culture-motivated pragmatic acts (practs) and contextual features of language use in the espousal of cultural issues in the selected plays of Yerima, with a view to establishing their cultural relevance. The study adopts Jacob Mey‟s theory of pragmeme, which accounts for context-ingrained utterances within social and cultural bounds. Six plays of Yerima‟s cutting across the cultural practices of the three major ethnic groups in Nigeria were purposively selected: Mu’adhin’s Call and Attahiru (Hausa culture), Mojagbe and Ajagunmale (Yoruba culture), Idemili and Akuabata (Igbo culture). Eight hundred and twenty-eight culture-based conversations in the plays were purposively selected from the texts: Mu’adhin’s Call -128; Attahiru- 122, Idemili-112, Akuabata-119, Mojagbe-182, and Ajagunmale-175. Data were subjected to pragmatic analysis. Eighteen practs and allopracts occur in the selected texts: explaining, informing, warning/cautioning, accusing, rebuking, persuading, insisting, assuring, praising, appealing, declaring, pleading, advising, condemning, inviting, confessing, invoking and lamenting. These are situated in three types of contexts: communal, traditional and emotive, to espouse different cultural issues in the play. Four main common ground features characterise the data: shared cultural knowledge, shared situational knowledge, reference and voice, indexed by metaphors and proverbs. Eight of the practs and allopracts cut across the six plays sampled, namely, explaining, assuring, informing, warning/cautioning, accusing, rebuking, persuading and praising. Ten practs occur exclusively in particular texts: two in Mojagbe: invoking which addresses the Yoruba concepts of immortality, death and reincarnation, within the traditional context; and lamenting which topicalises the Yoruba expression of grief in emotive context; two in Ajagunmale: pleading, which handles morality; and insisting, which deals with the subject of punishment in traditional context. Three are found in Mu’adhin’s Call: confessing, declaring and condemning which topicalise the Hausa concept of royalty in traditional context; one in Attahiru: advising, which addresses the Hausa philosophy of valiancy within traditional context. One is noticed in Akuabata: appealing, treating social crisis and patience in traditional Igbo context; and one in Idemili: inviting, which handles the Igbo concept of familial bonding, situated in emotive context. Overall, in Mojagbe and Ajagunmale, practs orient largely to Yoruba cultural predeterminism and communalistic checks and balances; in Ma’adhin’s Call and Attahiru, the language generally practs Hausa cultural directness; and in Akuabata and Idemili, utterances express the Igbo cultural accommodation and filial attachment. Ahmed Yerima engages language within emotive, communal and traditional contexts in practing culture-constrained acts, which border on particular cultural practices of the Yoruba, Hausa and Igbo. Thus, there is a motivated relationship between his pragmatic engagements and major Nigerian cultures